The Degree of Principals' Evaluation of Methods Used by Basic Stage Teachers For Promoting Students' Ethical Values - Zamel, Majdi (Jordan Journal of Educational Sciences, 2017)
The current study aimed to identify the degree of principals' evaluation of methods used by teachers of basic stage schools for promoting students' ethical values in Tulkarm schools. Moreover, the study aimed to activate these methods among male and female teachers of the basic stage. To achieve this aim, a 38-item questionnaire was constructed and administered to (50) male and female principals in the second semester of the school year 2015/2016 in Tulkarm city. The statistical analysis of the data revealed that the total degree of principals' evaluation of teachers' methods scored a high level of (3.94). Additionally, the results showed differences in principals' evaluation attributed to years of experience and the number of training courses. However, the results revealed slight differences in the means of principals' evaluation, attributed to principals’ gender, educational level and specialization. The study recommended integrating the ethical values into the school curriculum, in addition to encouraging teachers to employ more in-class and out-class activities. On the other hand ,the study recommended carrying out further studies in this particular field